Tonic Immobility Is Influenced by Starvation, Life Stage, and Body Mass in Ixodid Ticks. Issue 3 (16th February 2021) - Oyen, Kennan J; Croucher, Lillian; Benoit, Joshua B
Abstract: The ability to escape predation modulates predator–prey interactions and represents a crucial aspect of organismal life history, influencing feeding, mating success, and survival. Thanatosis, also known as death feigning or tonic immobility (TI), is taxonomically widespread, but understudied in blood-feeding vectors. Hematophagous arthropods, such as ticks, are unique among animals as their predators (birds, mice, lizards, frogs, and other invertebrates) may also be their source of food. Therefore, the trade-off between predator avoidance and host-seeking may shift as the time since the last bloodmeal increases. Because ticks are slow-moving and unable to fly, or otherwise escape, we predicted that they may use TI to avoid predation, but that TI would be influenced by time since the last bloodmeal (starvation). We therefore aimed to quantify this relationship, examining the effect of starvation, body mass, and ontogeny on TI for two tick species: Dermacentor variabilis (Say) (Acari: Ixodidae) and Rhipicephalus sanguineus (Latreille) (Acari: Ixodidae). As we predicted, the duration and use of TI decreased with time since feeding and emergence across species and life stages. Therefore, ticks may become more aggressive in their search for a bloodmeal as they continue to starve, opting to treat potential predators as hosts, rather than avoiding predation by feigning death. Antipredator behaviors such as TI may influence the intensity and amount of time ticks spend searching for hosts, driving patterns of tick-borne pathogen transmission. This identification and quantification of a novel antipredation strategy add a new component to our understanding of tick life history.